2013
DOI: 10.1007/s00380-013-0407-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma urokinase antigen and C-reactive protein predict angina recurrence after coronary angioplasty

Abstract: This study evaluates the predictive value of several biochemical indices of the coagulation-fibrinolysis system, platelet function, and inflammatory state for angina recurrence after successful percutaneous transluminal coronary angioplasty (PTCA). We measured preprocedural and follow-up plasma levels of C-reactive protein (CRP), fibrinogen, and urokinase plasminogen activator antigen (uPA), plasminogen activator inhibitor-1 (PAI-1) activity, tissue plasminogen activator activity, and adenosine diphosphate-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Associations between the levels of PTX-3, hs-CRP and adiponectin and the presence or severity of CAD An increase in CRP can predict future cardiovascular events [14,15]. Martijn et al [16] reported a positive association between plasma levels of CRP and major cardiovascular events in patients with intermediate lesions in whom percutaneous coronary intervention was deferred based on a normal fractional flow reserve.…”
Section: Discussionmentioning
confidence: 98%
“…Associations between the levels of PTX-3, hs-CRP and adiponectin and the presence or severity of CAD An increase in CRP can predict future cardiovascular events [14,15]. Martijn et al [16] reported a positive association between plasma levels of CRP and major cardiovascular events in patients with intermediate lesions in whom percutaneous coronary intervention was deferred based on a normal fractional flow reserve.…”
Section: Discussionmentioning
confidence: 98%